Fabrikasi Cor Ornamen Kursi Taman Ukuran Tinggi 80cm, Lebar 70cm, Tebal 4cm, Kapasitas 0,5 Biji/Jam - Yohanes Yuda Kristianto; Syamsul Hadi; Sholeh Aditya Tri Eriansyah; Ignatius Nicholas; Aditya Zalfa Prayoga (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2026)
The non-ergonomics of garden chairs for users, the lack of strength of garden chairs made of gray cast iron, and the lack of production efficiency are the problems faced. The purpose of fabrication is to obtain a gray cast iron garden chair measuring 80 cm high, 70 cm wide, 4 cm thick which is ergonomic, strong enough, and efficient in its production process. The fabrication method includes: processing of student anthropometric data, determining material strength using the beam theory approach, determining freezing time using Chvorinov's theory, designing garden chairs, making sand casting using green sand molds, preparing gray cast iron raw materials, melting gray cast iron, pouring molten metal into molds and cooling, dismantling the mold and cutting the casting bowl and riser, finishing, and checking quality and dimensions. The fabrication results are in the form of a gray cast iron garden chair measuring 80 cm high, 70 cm wide, 4 cm thick which is ergonomic, strong enough, and efficient in its production process, the total production cost is IDR 640,000/unit, the production process duration is 120 minutes/unit with the implication that the garden chair is comfortable to use and strong enough for the weight of the person sitting on it.